Metab2MeSH: annotating compounds with medical subject headings - Sartor, Maureen A.; Ade, Alex; Wright, Zach; States, David; Omenn, Gilbert S.; Athey, Brian; Karnovsky, Alla (Bioinformatics (Oxford, England), 2012)
Progress in high-throughput genomic technologies has led to the development of a variety of resources that link genes to functional information contained in the biomedical literature. However, tools attempting to link small molecules to normal and diseased physiology and published data relevant to biologists and clinical investigators, are still lacking. With metabolomics rapidly emerging as a new omics field, the task of annotating small molecule metabolites becomes highly relevant. Our tool Metab2MeSH uses a statistical approach to reliably and automatically annotate compounds with concepts defined in Medical Subject Headings, and the National Library of Medicine's controlled vocabulary for biomedical concepts. These annotations provide links from compounds to biomedical literature and complement existing resources such as PubChem and the Human Metabolome Database. Availability:  http://metab2mesh.ncibi.org Contact:  akarnovs@umich.edu Supplementary information:  Supplementary data are available at Bioinformatics online.